Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Dan Insentif Terhadap Produktivitas Kerja Karyawan (Studi Pada UD. Alfa Harapan Tenggarang Bondowoso) - Alfiah Alfiah; Abdul Kodir Djaelani; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Every agency or company always strives for employees to provide maximum work productivity to achieve a goal within a company. One such company is UD. Alpha Hope. The aim of this type of explanatory research and quantitative approach is to identify and analyze leadership styles, work motivation, and incentives on work productivity, either simultaneously or partially. Sampling used a saturated sampling technique where all members of the population were sampled so that 44 respondents were obtained. This research method uses multiple linear regression analysis with the SPSS analysis tool. Based on the results of this study, leadership style, work motivation, and incentives simultaneously and partially have an influence on work productivity. Keywords: Leadership Style, Work Motivation, Incentives, Work Productivity